Symbolic interaction and new social media - Johns, Mark D.; Chen, Shing-Ling.; Terlip, Laura A. (Bingley, U.K. : Emerald, 2014)
The new social media build on and further complicate all of the issues and processes of symbolic interaction. This volume builds on and expands the existing symbolic interactionist perspective to include the study of social interaction made possible by the use of new social media. This special issue demonstrates the interface between willful social interaction and structured technological featureshow social media are defined by social interactions, as well as how social interactions are dictated by the use of social media.
When McLuhan met Simmel : form is the content, medium is the message / Shing-Ling S. Chen, Mark D. Johns, Laura A. Terlip -- From object to flow : network sensibility, symbolic interactionism, and social media / Annette N. Markham, Simon Lindgren -- Social network analysis for Facebook : locating cliques and visualizing sociability / Jeffrey Coons, Shing-Ling S. Chen -- New Iowa school redux : Second Life / Michael A. Katovich, Shing-Ling S. Chen -- Mutable selves and digital reflexivities : social media for social change in the Middle East and North Africa / Lara Lengel, Victoria Ann Newsom -- Structural roles in Massively Multiplayer Online Games : a case study of guild and raid leaders in World of Warcraft / J. Patrick Williams, David Kirschner, Zahirah Suhaimi-Broder -- (Re)embodiment of the digital self and first life body in a new social media environment : paid sex work in Second Life / Justin A. Martin -- Surfing to an alternative self : internet technology and sexuality among 'married straight homosexual men' / Avi Shoshana -- "The wall is the city" : a narrative analysis of Vancouver's post-riot "apology wall" / Jennifer A.A. Lavoie, Judy Eaton, Carrie B. Sanders, Matthew Smith.
Print version record
Keywords: Social Science -- Sociology -- General; Social interaction; Society & culture: general; Social media -- Psychological aspects; Symbolic interactionism; Social interaction -- Technological innovations